2011
DOI: 10.1016/j.otsr.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Occupational outcome after surgery in patients with a rotator cuff tear due to a work-related injury or occupational disease. A series of 262 cases

Abstract: Level IV - Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 20 publications
2
42
1
Order By: Relevance
“…Different proportions of patients involved in strenuous physical labor in the study groups may have influenced the return-to-work rates. In the current study, 61.9% of subjects did heavy work, compared with 68.3%, 6) 61.5%, 8) and 35.6% 9) in prior studies. Moreover, the definition of strenuous physical labor differed among the studies.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Different proportions of patients involved in strenuous physical labor in the study groups may have influenced the return-to-work rates. In the current study, 61.9% of subjects did heavy work, compared with 68.3%, 6) 61.5%, 8) and 35.6% 9) in prior studies. Moreover, the definition of strenuous physical labor differed among the studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Univariate analysis indicated that preoperative heavy work, defined as occupations requiring repetitive overhead activities 6) or lifting of heavy items, 8) and workers' compensation were significantly associated with return to work (P <0.01). Multivariate stepwise logistic regression analysis revealed that preoperative heavy work and female sex were significantly associated with return to work (P <0.05; Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations